Foundational films : early cinema and modernity in Brazil - Conde, Maite, 1971- (University of California Press, 2018)
"In her authoritative new book, Maite Conde introduces readers to the crucial early years of Brazilian cinema. Focusing on silent film released during the First Republic (1889-1930), Foundational films explores how the medium became implicated in a larger project to transform Brazil into a modern nation. Analyzing an array of cinematic forms, from depictions of contemporary life, to fan magazines, to experimental avant-garde productions, Conde demonstrates the distinct ways in which Brazil's early film culture helped to project a new image of the country"--Provided by publisher.
Keywords: Motion pictures -- Brazil -- History -- 20th century.; Motion pictures -- Brazil -- History -- 19th century.; Silent films -- Brazil.; Brazil -- In motion pictures.; Cinéma -- Brésil -- Histoire -- 20e siècle.; Cinéma -- Brésil -- Histoire -- 19e siècle.; Films muets -- Brésil.; Brésil -- Au cinéma.; PERFORMING ARTS -- Reference.; HISTORY -- Latin America -- General.; Motion pictures; Silent films; Brazil; 1800-1999; Electronic books.; History